PENDAMPINGAN USAHA MIKRO KECIL DAN MENENGAH DALAM PEMBUATAN MEDIA PROMOSI PADA USAHA PENGASAPAN LELE DI DESA NGRANTI KECAMATAN BOYOLANGU KABUPATEN TULUNGAGUNG - Mufida Diah Lestari; Chusnatul Ulaela Sajali; Choirul Anwar; Rendi Agung Setiono; Tia Sri Wulandari (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tulungagung, 2024)
Micro, small and medium enterprises (MSMEs) are a type of business that can contribute to the economy of small communities. One of the efforts that can be made is to develop household-scale businesses in each residential area. The amount of sales income from this business can help increase people's income in certain areas. One of the businesses run by the community in Ngranti Village, Boyolangu District, Tulungagung Regency is to create a household scale industry, namely smoked catfish, but as the business develops, it does not make a big contribution to the economy of the community in Ngranti Village. This is due to several things, including the level of human resources (HR) in society which are not digitally savvy enough so they are not yet able to market their products using modern methods, namely online systems. This effort is interesting because of the need for assistance so that this provides the aim of this community service activity, namely by providing assistance to micro, small and medium enterprises in making promotional media for catfish cooking in Ngranti Village, Boyolangu District, Tulungagung Regency. As a result of this assistance, it is hoped that there will be a change in the marketing method for smoked catfish to become more modern so that it will increase sales of their products by expanding the market. The increased sales proceeds will provide increased welfare for the community in Ngranti Village, Boyolangu District, Tulungagung Regency.